Therapist: Development of a Mobile Application on Emotional Control Guidance and Mood Charts for University Students - Tan, Jasline Jia Yi; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2023)
Emotional control refers to the ability to understand and manage our emotions, while a mood chart is a tool that records a person's mood at regular intervals. In this competitive era, university students are the individuals who are full of emotional pressure. However, Malaysian university students’ mental health is exacerbated by their insufficient emotional awareness. Hence, a mobile application proposed namely “Therapist” is needed to provide guidance for emotional control and mood charts for assisting university students based on DASS-21 psychological inventory model and the functional testing will be performed to target users. Multimedia Mobile Content Development (MMCD) approach is used to develop Therapist mobile application. The usability testing has resulted in a score of 86.25 which is within the acceptable range based on the System Usability Scale (SUS). Therefore, it can be concluded that the Therapist application can be used as an emotional guidance and mood chart recorder.